LITERASI DEMOKRASI DAMAI DI ERA DIGITAL PADA PERWAKILAN PELAJAR SMPN 4 SURAKARTA - Haqqu, Rizca; Mahadian, Adi Bayu; Satria Putri, Berlian Primadani (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2023)
Based on the information from the Principal of SMPN 4 Surakarta, many of her students experienced bullying when using social media and inappropriately expressed their freedom of opinions. As a result, a team of lecturers from the Faculty of Communication and Business, Telkom University conducts a Community Service Activity at SMPN 4 Surakarta entitled